Potential Conﬂict Among ASEAN Member States in The Implementation of The ASEAN Economic Community - Sugiarto Pramono; Anna Yulia Hartati; Adi Joko Purwanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
The ﬁndings in this article defy the common assumption that the free market, including the formation of the ASEAN Economic Community (AEC) in Southeast Asia, is correlated with the creation of a spillover and complex interdependency, reducing conﬂicts between countries in the region. This ﬁnding could well contribute as a theory in the academic sphere and as policies in the practical world. The author uses a theoretical framework of structural realism to explain the potential conﬂict between countries of the Southeast Asian region. There are four potential conﬂict situations among countries in the implementation of AEC: ﬁrstly, the structure of economic disparity. This situation would construct an identity of in-group – out-group or “us” versus “them” in the context of who gains and loses in the AEC. Secondly, similarity of natural resources. This fact led the Southeast Asian countries to compete and create standardization wherein each party is in hostile competition to claim valid ﬁndings and arguments associated with eﬀorts to reduce or stop the ﬂow of imports into their respective countries. Thirdly, competition among businesses, in which AEC constructed free market could potentially provoke the emergence of regional trading cartel. Fourthly, the structure of military power. Historical records show that any economic growth occurring in a country will be accompanied by the growth of its military budget.